2005
DOI: 10.1038/sj.bjc.6602912
|View full text |Cite
|
Sign up to set email alerts
|

Increased level of chromosomal damage after irradiation of lymphocytes from BRCA1 mutation carriers

Abstract: Deleterious mutations in the BRCA1 gene predispose women to an increased risk of breast and ovarian cancer. Many functional studies have suggested that BRCA1 has a role in DNA damage repair and failure in the DNA damage response pathway often leads to the accumulation of chromosomal aberrations. Here, we have compared normal lymphocytes with those heterozygous for a BRCA1 mutation. Short-term cultures were irradiated (8Gy) using a high dose rate and subsequently metaphases were analysed by 24-colour chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
(12 reference statements)
2
19
0
Order By: Relevance
“…Subsequent studies failed to confirm such a finding (Baria et al, 2001;Baeyens et al, 2004;Kotsopoulos et al, 2007). Using chromosomal rearrangements to evaluate the sensitivity to genotoxic stress, a significantly higher level of chromosomal damage in the BRCA1 þ /À lymphocytes compared with normal controls was found after irradiation (Kote-Jarai et al, 2006). On the other hand, Baeyens et al (2004) found that there is no significant difference in the frequency of chromosomal breakages between breast cancer patients with and without a BRCA1 mutation.…”
Section: Introductionmentioning
confidence: 71%
“…Subsequent studies failed to confirm such a finding (Baria et al, 2001;Baeyens et al, 2004;Kotsopoulos et al, 2007). Using chromosomal rearrangements to evaluate the sensitivity to genotoxic stress, a significantly higher level of chromosomal damage in the BRCA1 þ /À lymphocytes compared with normal controls was found after irradiation (Kote-Jarai et al, 2006). On the other hand, Baeyens et al (2004) found that there is no significant difference in the frequency of chromosomal breakages between breast cancer patients with and without a BRCA1 mutation.…”
Section: Introductionmentioning
confidence: 71%
“…In a recent publication from the UK, the mean number of chromosomal aberrations (translocations and breaks) per metaphase cell were scored at 24 h, and 6 days following high-dose irradiation (8 Gy). After 6 days, chromosomal damage was found to be significantly higher in lymphocytes from heterozygous BRCA1 mutation carriers compared with normal controls (average number of aberrations per mitosis was 3.5 for cases and 1.6 for controls, P ¼ 0.0001) (Kote-Jarai et al, 2006). No difference in aberrations was detected at 24 h post-irradiation.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, an impaired cellular response to DNA damage appears to be a plausible mechanism whereby BRCA1 mutation carriers are at an increased risk of breast cancer (Scott, 2004). Hence, the evaluation of an individual's capacity to repair DNA may serve as a biomarker of breast cancer risk in carriers of these mutations.Two previous studies have shown higher levels of chromosomal aberrations and chromosomal breaks among women with a BRCA1 mutation compared with non-carrier controls (Kowalska et al, 2005;Kote-Jarai et al, 2006); however, these cytogenetic assays are laborious and expensive. The aim of the current paper was to elucidate a relatively simple and inexpensive biomarker of breast cancer susceptibility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, a number of studies have addressed BRCA1 haploinsufficiency in lymphoid cells, Epstein-Barr virus-immortalized lymphoid cell lines, and fibroblasts derived from BRCA1 carriers. Many of these studies described phenotypes specific to the cells carrying heterozygous BRCA1 mutations (36)(37)(38)(39)(40). However, other studies failed to detect differences between cells from BRCA1 carriers and controls (41)(42)(43), and thus BRCA1 haploinsufficiency in the above-mentioned cell types has been controversial (13,44,45).…”
Section: Discussionmentioning
confidence: 98%